Can directors’ and officers’ liability insurance improve corporate ESG performance? - Xu, Hanyou; Zhao, Jing (Frontiers in Environmental Science, 2022)
Directors’ and Officers’ liability insurance (abbreviated as “D&O insurance”) was born in the United States in the 1930s and has been widely used in Western countries. In contrast, China introduced D&O insurance in 2002, and its development has been relatively slow. With the revision and improvement of Chinese regulatory laws and regulations, such as the new Securities Law in March 2020, which further regulates the obligations and responsibilities of corporate management, and increases the penalties for information disclosure violations of listed companies, the risk to directors and executives performing their duties is promoted. This makes D&O insurance the focus of China’s capital market, with huge potential for future development. Therefore, it is of urgent practical importance to study the impact of director liability insurance on corporate governance in China. At the same time, D&O insurance, as an effective risk management mechanism, has not yet reached a unified conclusion in the academic circles on its corporate governance effectiveness. On the one hand, D&O insurance may encourage directors and senior executives to be proactive to enhance the company’s market value by taking risks, and on the other hand, it may induce opportunistic behavior of managers and reduce the company’s value. Under the new development form, analyzing and researching the governance effect of D&O insurance from different angles will help to provide a theoretical basis for its further development and popularization in China’s capital market. Thus, using a sample of Chinese A-share listed companies from 2011 to 2020, this study investigates the impact of D&O insurance on corporate ESG performance. The results show that D&O insurance significantly improves corporate ESG performance. Additional analysis suggests that the contribution of D&O insurance to ESG performance is achieved by improving independent director function-performing effectiveness and increasing corporate risk-taking. The findings of this paper have policy implications for a better understanding of the governance role of D&O insurance, encouraging companies to improve corporate ESG performance.